Answer:
(x-1)^2 + (y+1)^2 = 0.25
Explanation:
The equation of a circle is given by (x-h)^2 + (y-k)^2 = r^2
(h,k) is the center of the circle, and r is the radius.
Looking at the circle, the center is at (1,-1), so h = 1, and k = -1. Add that to our equation, you get:
(x-1)^2 + (y+1)^2 = r^2
Now, we need to find the radius. Since the center of the circle is at x = 1, and a point on the edge of the circle is at x = 0.5, we can subtract these to get the radius. 1 - 0.5 = 0.5. Adding the radius to our equation, we get:
(x-1)^2 + (y+1)^2 = 0.5^2
Simplifying by squaring the 0.5:
(x-1)^2 + (y+1)^2 = 0.25